Author, scribe, and book in late medieval English literature - Critten, Rory G. (D.S. Brewer is an imprint of Boydell & Brewer Ltd., 2018)
Thomas Hoccleve, Margery Kempe, John Audelay and Charles d'Orleans present themselves as the makers not only of their texts, but also of the books that transmitted their writing. This new study argues that they elaborated a "self-publishing pose" with the aim of regaining their audiences' confidence in the face of the compromised social, physical and material conditions they inhabited. Dr Critten shows that while the strategies of self-presentation that these authors develop draw on trends in contemporary literature and book history (such as the proliferation of the "go, litel bok" motif and the increasing popularity of the single-author codex), their approach to writing differs fundamentally from that pursued by their immediate predecessors, Chaucer and Gower, and by their most prominent peer, Lydgate. Rather, in their unusual insistence on their co-identity with their manuscripts, they demonstrate a new awareness of the socially instrumental potential of Middle English writing